Detailed Joint Region Analysis of the 7-Joint Ultrasound Score: Evaluation of an Arthritis Patient Cohort over One Year. (12th August 2013) - Ohrndorf, S.; Halbauer, B.; Martus, P.; Reiche, B.; Backhaus, T. M.; Burmester, G. R.; Backhaus, M.
Abstract : Objective . The main objective of this study was to evaluate the 7-joint ultrasound (US7) score by detailed joint region analysis of an arthritis patient cohort. Methods . The US7 score examines the clinically most affected wrist, MCP and PIP II, III, MTP II, and V joints for synovitis, tenosynovitis/paratenonitis, and erosions. Forty-five patients with rheumatoid arthritis (RA) (84.4%) and spondyloarthritis with polyarticular peripheral arthritis (PsA 13.3%; AS 2.2%) with a median disease duration of 6.5 yrs (range 7.5 mths–47.6 yrs) were included and examined at baseline and 3, 6, and 12 months after starting or changing therapy (DMARD/biologic). In this study, detailed US7 score joint region analysis was firstly performed. Results . The joint region analysis performed at baseline disclosed synovitis in 95.6% of affected wrists in the dorsal aspect by greyscale (GS) US where Grade 2 (moderate) was most often (48.9%) detected. Palmar wrist regions presented Grade 1 (minor) capsule elevation in 40% and Grade 2 (moderate synovitis) in 37.8%. Tenosynovitis of the extensor carpi ulnaris (ECU) tendon was found in 40%, with PD activity in 6.6%. Most of the erosions in MCP II were detected in the radial (68.9%), followed by the dorsal (48.9%) and palmar (44.4%) aspects. In MTP V, erosions were seen in 75.6% from lateral. Conclusions . Synovitis in GSUS was more often detected in the wrist in the dorsal than in the palmar aspect. ECU tendon involvement was frequent. Most erosions were found in the lateral scan of MTP V and the medial (radial) scan of MCP II.